Caracterización de la vegetación y el microclima en Sistemas Agroforestales de café (Coffe arabica L.) en tres pisos altitudinales en la zona cafetera Chaguarpamba-Olmedo. - Sarango Acaro, Tania Yasmin (2018)
It is an analysis of the characteristics of the arboreal vegetation, shrub and, the microclimate of the Agroforestry Coffee Systems (Coffea arabica L.); and, its relation with the requirements of the cultivation in the Chaguarpamba-Olmedo coffee zone. With a sampling of plant populations, using three plots of 600 m² in each site. Established in three altitudinal floors: Lobongo at 1 719 m s. n. m., Chaguarpamba to 1 459 m s. n. m. and Lozumbe at 850 m. n. m. Variables were evaluated: height, crown diameter and relative frequency, relative density and IVIs (Simplified importance value index) were calculated; climatic variables: intensity of light, air temperature, relative humidity (HR) and wind speed. The data was processed and analyzed for the simple variance and Pearson correlations using Excel software and Infostat. The results indicated that the systems were not similar in both their composition and microclimatic conditions. The main species present in the agroforestry systems apart from the Coffea agricultural interest crop were: in Lozumbe there were 18 species, with Musa, Inga and Myrsine being the most representative, with shadow of 63.80%, temperature of 25.9 °C , RH of 68 % and wind of 0.4 m/s; in Lobongo the presence of Musa Acacia and Inga stands out, with a shadow percentage of 60.26 %, temperature of 26.9 °C, HR of 59 % and wind 0.3 m / s; finally in the Chaguarpamba site, the presence of Musa and Solanum with shadow of 24.75 %, temperature of 22.8 °C, HR of 68 % and wind of 0.4 m/s. The characteristics of both the vegetation and the microclimate determined the lack of uniformity within each site and between them. KEY WORDS: agroforestry, Coffea, climate, vegetation